Solution-based synthesis of wafer-scale epitaxial BiVO4 thin films exhibiting high structural and optoelectronic quality. Issue 22 (22nd April 2022) - Kunzelmann, Viktoria F.; Jiang, Chang-Ming; Ihrke, Irina; Sirotti, Elise; Rieth, Tim; Henning, Alex; Eichhorn, Johanna; Sharp, Ian D.
Abstract : Epitaxial, (010)-oriented BiVO4 films on 2′′ wafers synthesized by spin-coating and metalorganic decomposition exhibit remarkably high crystal quality. Spectroscopy reveals a large uniaxial optical anisotropy, confirming theoretical predictions. Abstract : We demonstrate a facile approach to solution-based synthesis of wafer-scale epitaxial bismuth vanadate (BiVO4 ) thin films by spin-coating on yttria-stabilized zirconia. Epitaxial growth proceeds via solid-state transformation of initially formed polycrystalline films, driven by interface energy minimization. The (010)-oriented BiVO4 films are smooth and compact, possessing remarkably high structural quality across complete 2′′ wafers. Optical absorption is characterized by a sharp onset with a low sub-band gap response, confirming that the structural order of the films results in correspondingly high optoelectronic quality. This combination of structural and optoelectronic quality enables measurements that reveal a strong optical anisotropy of BiVO4, which leads to significantly increased in-plane optical constants near the fundamental band edge that are of particular importance for maximizing light harvesting in semiconductor photoanodes. Temperature-dependent transport measurements confirm a thermally activated hopping barrier of ∼570 meV, consistent with small electron polaron conduction. This simple approach for synthesis of high-quality epitaxial BiVO4, without the need for complex deposition equipment, enables a broadly accessible materials base to accelerate research aimed at understanding and optimizing photoelectrochemical energy conversion mechanisms.